Iron Deficiency in Palms: ENH 1013/EP265, 9/2005 - Broschat, Timothy K. (EDIS, 2019)
This document is ENH 1013, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date September 2005. ENH 1013/EP265: Iron Deficiency in Palms (ufl.edu)